2021
DOI: 10.2147/ijnrd.s319933
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urinary Beta 2 Microglobulin and Kidney Injury Molecule-1 in Predicting Kidney Function at One Year Following Acute Kidney Injury

Abstract: Background: There is only limited information on the utility of urinary biomarkers in predicting long-term kidney function following acute kidney injury (AKI). The current study assessed whether urinary beta 2 microglobulin/creatinine (B2M/creat) and kidney injury molecule-1/creatinine (KIM-1/creat) ratios, measured in the early recovery phase of AKI, are predictive of kidney function at one year. Methods: This is a prospective study done in a tertiary care centre in South India, from March 2017 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…These characteristics have made blood B2M a suitable marker for evaluating renal function in AKI and CKD. Urinary B2M levels rise early during the course of nephrotoxicity mediated AKI in rat models and revert to normal during the healing phase [ 80 ].…”
Section: Emerging Novel Biomarkers For Detecting Acute Kidney Injurymentioning
confidence: 99%
“…These characteristics have made blood B2M a suitable marker for evaluating renal function in AKI and CKD. Urinary B2M levels rise early during the course of nephrotoxicity mediated AKI in rat models and revert to normal during the healing phase [ 80 ].…”
Section: Emerging Novel Biomarkers For Detecting Acute Kidney Injurymentioning
confidence: 99%
“…The majority of studies conducted so far have looked at serum b2M rather than urine concentrations [5,18]. Most of them pointed to elevated β2M level in patients after chemotherapy with nephrotoxic agents and emphasized its high utility in detecting chemotherapy-induced acute kidney injury [14,24]. On the other hand, there are very limited data on the utility of urinary β2M in diagnosing the onset of CKD associated with anticancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff point for urinary β2MG for the prediction of positive DMSA (technetium Tc 99m dimercaptosuccinic acid) scan was 0.8 mg, but it was not enough sensitive (40.9%) and specific (84.1%) to be used as a diagnostic marker for the prognosis of renal injury (51). Recently, Puthiyottil et al (52) showed that in adult patients who remained alive after AKI, the urinary β2MG/creatinine ratio at 2 weeks was higher compared to control group, and it is predictive of low estimated glomerular filtration rate at 1 year. Furthermore, urine level β2MG in resuscitated patients after cardiac arrest at admission and day 3 were independently associated with high risk of AKI, mortality, and poor neurological outcome in a study published by Beitland et al (53).…”
Section: Novel Biomarkers Of Kidney Injury Neutrophil Gelatinase-asso...mentioning
confidence: 99%